Possible mechanism of action of Mentha Arvensis in cardiovascular diseases - Gul , Saima; Gul , Humaira; Nawaz , Rukhsana (International Journal of Endorsing Health Science Research, 2014)
Mentha arvensis (MA) is traditionally used in hypertension and in patients with ischemic heart disease. The scientific rationale for its use is not known. In order to find a pharmacological basis of its use in traditional medicine we made three polarity based fraction from the crude extract of MA and investigated their effects on arachidonic acid metabolism. MA inhibited arachidonic acid metabolite thromboxane B2-a stable analogue of thromboxane-A2, formed via cyclooxygenase pathway and lipoxygenase product 1 and 12-hydroxyeicosatetraenoic acid formed via lipoxygenase pathway. More potent inhibition of thromboxane-B2 compared to lipoxygenase product 1 and 12-hydroxyeicosatetraenoic acid was observed and indicates MA might possess antiplatelet activity as thromboxane-B2 is one of the strongest proponents of platelet aggregation. When MA was investigated for antiplatelet activity, it was found to inhibit human platelet aggregation induced by arachidonic acid as well as by adenosine diphosphate and platelet activating factor while collagen-induced platelet aggregation was unaffected by MA. Since arachidonic acid-induced aggregation is mediated through thromboxane-A2, these results indicate that inhibition of platelet aggregation may be responsible for the observed beneficial effects of MA in patients with ischemic heart disease. Furthermore, MA was also effective in enhancing glutathione peroxidase activity, although it had no significant effect on superoxide dismutase activity. These activities were however, distributed throughout various fraction of MA.